Facile surfactant- and template-free synthesis and luminescence properties of needle-like calcite CaCO3:Eu3+ phosphors. Issue 4 (4th January 2018) - Dai, Yunzhi; Zou, Haifeng; Zhu, He; Zhou, Xiuqing; Song, Yanhua; Zheng, Keyan; Shi, Zhan; Sheng, Ye
Abstract : Simulated diagram of the growth process of needle-like CaCO3 :Eu 3+ particles. Abstract : Needle-like CaCO3 :Eu 3+ calcite phosphors have been successfully synthesized by a simple carbonization method in an ethylene glycol–H2 O system without using any surfactant, catalyst, or template. The as-obtained samples were characterized by means of XRD, FT-IR, SEM, TEM, HRTEM, SAED, and PL techniques. The XRD and FT-IR results demonstrate that the product is a pure calcite phase. The SEM and TEM images indicate that the morphology of the as-prepared calcite CaCO3 :Eu 3+ nanoparticles is needle-like. The possible formation mechanism of the needle-like CaCO3 :Eu 3+ calcite has been proposed based on a series of pH-dependent experiments. The needle-like CaCO3 :Eu 3+ calcite nanoparticles exhibit much stronger red emission under UV light excitation than cubic and spindle-like CaCO3 :Eu 3+ calcite nanoparticles.